IMPACT OF INTEGRATION INTO FOREIGN MARKETS ON THE REGIONAL ECONOMY AND THEORETICAL APPROACHES TO IT (Marketing Journal, 2025)
Mazkur maqolada iqtisodiy integratsiyaning mazmun -mohiyati, uning iqtisodiy rivojlanishdagi ahamiyati, shuningdek tashqi bozorlarga integratsiyalashuv va uning mintaqaviy iqtisodiy oʻsishga taʼsiri xususida fikr yuritiladi.
Keywords: economic integration; economic growth; foreign trade; concepts; regional economy; market; policy; trade; strategy; system